Childhood maltreatment patterns and suicidal ideation: mediating roles of depression, hope, and expressive suppression. - Ye, Yingying; Chen, Bo; Zhen, Rui; Li, Yifan; Liu, Zhengyi; Zhou, Xiao (European Child & Adolescent Psychiatry, 2024)
Childhood maltreatment has long-term negative effects on individuals' physical and mental well-being, and may increase the risk for suicidal ideation. However, how different patterns of childhood maltreatment affect subsequent suicidal ideation and the underlying mediating mechanisms remain unclear, particularly among Chinese adolescents. This study used latent profile analysis to identify patterns of childhood maltreatment among adolescents and explored how these patterns predicted subsequent suicidal ideation via depression, hope, and expressive suppression. This study used a two-wave, 1-year longitudinal design and included 2156 adolescents (Mage = 13.97 years, SDage = 1.61 years; 49.6% females). We identified three patterns of childhood maltreatment: low maltreatment, high psychological neglect, and high maltreatment. Compared with the low maltreatment group, the high maltreatment group indirectly predicted subsequent suicidal ideation 1 year later via depression through hope and expressive suppression, whereas the direct effect on suicidal ideation was not significant. Compared with the low maltreatment group, the high psychological neglect group had a significant direct effect on subsequent suicidal ideation and indirectly predicted suicidal ideation through depression or hope. Identifying patterns of childhood maltreatment among adolescents will assist mental health workers in developing targeted interventions to effectively alleviate suicidal ideation.